ילדים גנובים ותחליפים מפלצתיים: לילית כשדת-אם בכתבי יד יהודיים בענייני מאגיה ממזרח אירופה - גונדוס אנדראה (מחשבת ישראל, 2025)
A small number of East European manuscripts of magic and practical kabbalah enumerate recipes directed at disabling a specific function of Lilith focused on replacing or substituting a healthy human child with a disformed, physically, or mentally disabled demonic one. Designated by the Yiddish term, banem ביינעם (to replace or substitute), which appears in these manuscripts with an abundance of variant spellings exposing the influence of local dialects and diverse linguistic usage. As several recipes attest, the switching could occur either in utero or within a few weeks after birth. The wealth of magical formulas, designed to chain Lilith’s power to carry out child substitution or replacement, reflect pervasive anxieties among Jews concerning the mental and physical health of newborns. In constructing effective charms and amulets against Lilith, Jews in Eastern Europe drew on general Slavic beliefs, hagiographic folk traditions, and herbal cures to which they added specifically Jewish traditional, kabbalistic, and magical elements. The chapter will trace six types of curative options: nature-based formulas; the use of divine and angelic names, amplified by the ten sefirot; historiolae; diagrammatic-visual amulets; illocutionary speech acts; and combined formulas to highlight that concerns about children’s wellbeing comprised a shared cultural-religious space between Jews and their Slavic neighbors and occuped a place of vital importance for the care and wellbeing of Jewish family and communal life.